Somatic Mobilization: High Somatic Insertion Rate of mariner Transposable Element in Drosophila simulans - Mariana Cancian; Tiago Minuzzi Freire da Fontoura Gomes; Elgion Lucio Silva Loreto (Insects, 2022)
Although transposable elements (TEs) are usually silent in somatic tissues, they are sometimes mobilized in the soma and can potentially have biological consequences. The mariner element is one of the TEs involved in somatic mobilization (SM) in Drosophila and has a high rate of somatic excision. It is also known that temperature is an important factor in the increase of the mariner element SM in the fly. However, it is important to emphasize that excision is only one step of TE transposition, and the final step in this process is insertion. In the present study, we used an assay based on sequencing of the mariner flanking region and developed a pipeline to identify novel mariner insertions in Drosophila simulans at 20 and 28 °C. We found that flies carrying two mariner copies (one autonomous and one non-autonomous) had an average of 236.4 (±99.3) to 279 (±107.7) new somatic insertions at 20 °C and an average of 172.7 (±95.3) to 252.6 (±67.3) at 28 °C. In addition, we detected fragments containing mariner and others without mariner in the same regions with low-coverage long-read sequencing, indicating the process of excision and insertion. In conclusion, a low number of autonomous copies of the mariner transposon can promote a high rate of new somatic insertions during the developmental stages of Drosophila. Additionally, the developed method seems to be sensitive and adequate for the verification and estimation of somatic insertion.